On the Topological Nature of the Stable Sets Associated to the Second Invariant of the Order q Standard Lyness’ Equation
We prove a conjecture asserted in a previous paper (see [2]) about order q Lyness difference equation in R_*^+: u_n+q u_n=a+u_n+q-1+…+u_n+1, with a>0. It is known that the function on R_*^+